الصياغة الدستورية و أثرها على تفسيرات المحكمة الأتحادية العليا في العراق - ABDULRAHMAN, AVEEN KHALED (Journal of Duhok University, 2020)
The constitutional drafting stage is one of the stages in writing the constitution, which is aprocess of transferring ideas and principles from their philosophical-intellectual framework to alinguistic framework through a set of expressive words and methods or to make them implementvalid, and through fit drafting that able to reach the truth. there are many methods ofconstitutional drafting, between hard drafting which is specified to the obligation and judgment,and the soft drafting which is not specified that leaves the interpreter for discretionary authorityto interpret according to the circumstances and facts, as well as there is ambiguous drafting inwhich the intention of the legislator cannot be easily known and the fluctuating drafting inwhich the constitutional drafter handles to fix the same topic, but in different formulations,which leads to ambiguity of the intention of the legislator, and the drafter of the Iraqiconstitution in 2005 relied on more than one method in drafting the texts of the constitution, andwe show how some of these formulations had a negative impact on the decisions of the IraqiFederal Supreme Court when exercising its jurisdiction in interpreting the constitution untilsome of them generated a political and legal controversy at the same time.